Preparation of synthesis nanoparticles Fe3O4 based on iron sand Sumbawa - Bahtiar, Syamsul; Widyawati, Fauzi; Yanuar, Emsal; Ramadhan, Risky; Zahra, Karen; Hidayat, Syamsul (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Iron sand generally contains minerals such as ilmenite, magnetite, and hematite. Based on the results of previous tests, the main composition of iron sand in Rhee, Sumbawa regency, is magnetite. One method to increase the Fe content in iron sand is by pre-treatment with NaOH. NaOH is also used to precipitate heavy metals in a mineral. In this study, three variations were carried out with the ratio of NaOH: iron sand, namely: 1: 4, 2: 4, and 3: 4 at a temperature of 300 C. Furthermore, the calcination results were followed by the synthesis of Fe3O4 nanoparticles using the coprecipitation method. The results of the XRF characterization showed an increase in Fe levels after being processed by the alkalization treatment. The highest concentration was obtained in 1:4, with a Fe percentage of 91.1%. The results of the XRD characterization showed that the synthesis of Fe3O4 was successfully carried out with single phase Fe3O4 amlording to the data reference 96-9005839 forms and the space group F d -3 m. Crystal size analysis Using the Debey-Scherrer equation, the respective sizes were 12.7 nm, 8.71 nm, and 9.76 nm, respectively.